Parametric study of Stub-Beam Bolted Extended End-Plate connection to box-columns. (August 2020) - Mahjoob Behrooz, Sasan; Erfani, Saeed
Abstract: This paper aims to investigate different combinations of Bolted Extended End-Plate (BEEP) beam-to-column connections where the column sections are of the built-up box type. Therefore, some allowable combinations of beam-to-column subassemblages were chosen according to the AISC provisions, such as Strong Column-Weak Beam. Since the prequalified BEEP connections are generally attached to wide-flange column sections, there will be some complexities in the erection and bolts fastening processes involved where built-up box columns are used. One of these complexities is the closed inner space of such columns. Thus, a novel connection configuration is proposed to overcome these complexities. Hence, a number of 28 different connection subassemblages were modeled in ABAQUS finite element analysis software and tested under the connection qualification cyclic loading conditions. Hence, after verifying the numerical modeling's acceptable accuracy with two experimental models, the main proposed models were investigated, and their responses were evaluated. The results of this study indicate that this new proposed connection can satisfy the connection qualification criteria. However, further experimental studies are needed to be conducted to approve the practical use of this proposed connection. Highlights: A new alternative to connect beams to built-up box columns using BEEP connection is investigated. An accurate material constitutive model is used and verified against experimental models. All of the proposed models satisfy the AISC seismic provisions on connections' seismic behavior. The proposed stub beam transfers the stresses through the box-column web. The need for welding continuity plates in the box- columns is obviated.